Risk factors for critical limb ischemia in patients undergoing femoral cannulation for venoarterial extracorporeal membrane oxygenation: Is distal limb perfusion a mandatory approach?. (September 2019) - Kaufeld, Tim; Beckmann, Eric; Ius, Fabio; Koigeldiev, Nurbol; Sommer, Wiebke; Mashaqi, Bakr; Fleissner, Felix N; Siemeni, Thierry; Puntigam, Jacob Ono; Kaufeld, Jessica; Haverich, Axel; Kuehn, Christian
Background: Venoarterial extracorporeal membrane oxygenation support is a well-established tool in the care of severe refractory cardiac and respiratory failure. The application of this support may serve as a bridge to transplant, recovery or to implantation of a ventricular assist device. Venoarterial extracorporeal membrane oxygenation support can be administered through an open surgical access via the common femoral or axillary artery or a percutaneous approach using Seldinger technique. Both techniques may obstruct the blood flow to the lower limb and may cause a significant ischemia with possible limb loss. Malperfusion of the distal limb can be avoided using an ipsilateral distal limb perfusion, which may be established by adding a single-lumen catheter during venoarterial extracorporeal membrane oxygenation treatment to overcome the obstruction. The aim of this study is to distinguish the presence or absence of a distal limb perfusion regarding the incidence of distal limb ischemia. Furthermore, expected risk factors of open and percutaneous femoral venoarterial extracorporeal membrane oxygenation installation were evaluated for the development of distal limb ischemia. Methods: Between January 2012 and September 2015, 489 patients received venoarterial extracorporeal membrane oxygenation support at our institution. In total, 307 patients (204 male, 103 female) with femoral cannulation were included in the analysis. The cohort was distinguished by the presence (group A; n = 237) or absence (group B; n = 70) of a distal limb perfusion during peripheral venoarterial extracorporeal membrane oxygenation treatment. Furthermore, a risk factor analysis for the development of distal limb ischemia was performed. Results: The main indications for venoarterial extracorporeal membrane oxygenation therapy were a low cardiac output syndrome (LCOS) (53%) and failed weaning of extracorporeal circulation (23%). A total of 23 patients (7.49%) under venoarterial extracorporeal membrane oxygenation support developed severe distal limb malperfusion (3.38% in group A vs 21.42% in group B). Preemptive installation of distal limb perfusion extended the intervention-free intervals to 7.8 ± 19.3 days in group A and 6.3 ± 12.5 in group B. A missing distal limb perfusion (p = 0.001) was identified as a main risk factor for critical limb ischemia. Other comorbidities such as arterial occlusion disease (p = 0.738) were not statistically significantly associated. Surgical intervention due to vascular complications after extracorporeal membrane oxygenation explantation was needed in 14 cases (4.22% in group A and 5.71% in group B). Conclusion: We were able to identify the absence of distal limb perfusion as an independent risk factor for the development of critical distal limb ischemia during femoral venoarterial extracorporeal membrane oxygenation treatment. The application of a distal limb perfusion should be considered as a mandatory approach in the context of femoral venoarterial extracorporeal membrane oxygenation treatment regardless of the implantation technique.